Commonly Used Immunosuppressives Affect Mesenchymal Stem Cell Viability and Function: Should We Rethinking Clinical Trial Inclusion and Exclusion Criteria?. Issue 3 (19th August 2019) - Lightner, Amy L; Du, Zeji; Peterson, Timothy E; Shi, Ao; Li, Mark; Romero Arocha, Sinibaldo Rafael; Behfar, Atta
Abstract: Background: Clinical trials utilizing mesenchymal stem cells (MCSs) for the treatment of perianal Crohn disease are expanding. Most enrolled Crohn patients are being actively treated with corticosteroids, immunomodulators, and biologic therapy for their luminal and perianal disease at the time of enrollment and treatment. Aim: We sought to broaden the understanding of the effect of corticosteroids, immunomodulators, and biologic therapy on the viability and function of MCSs. This information is important for tailoring inclusion and exclusion criteria of clinical trials. Methods: Human adipose–derived mesenchymal stem cells (hAMCSs) were harvested and isolated from healthy patient donors. At Passage 3, hAMCSs were treated with 7 commonly used immunosuppressive therapies used to treat Crohn disease at increasing concentrations: dexamethasone, methotrexate, azathioprine, 6-mercaptopurine, infliximab, vedolizumab, and ustekinumab. Cell proliferation, migration, and cytokine secretion were analyzed at Day 4. Results: Dexamethasone and azathioprine and 6-mercaptopurien affected cell proliferation and migration. Dexamethasone even resulted in cell death at high physiologic concentrations. The same drugs also had the most profound impacts on IL-6, IL-8, and monocyte chemoattractant protein-1 secretion profiles. Biologic therapies, including anti-tumor necrosis factor, anti-interleukin, and anti-integrins, had the smallest impact on hAMSC proliferation, migration, and cytokine secretion profile. Conclusions: In clinical trials with MCSs, a washout period may be recommended for corticosteroids and immunomodulators to minimize any effect of systemic immunosuppression on MSC function and efficacy. Lay Summary: Researchers are investigating the effect of inflammatory bowel disease therapies on mesenchymal stem cells (MCSs), a novel emerging treatment for perianal fistulas in Crohn disease. Biologicals appear to be safe drugs without affecting the development of MCSs.